Dielectric properties of potassium carbonate‐impregnated cempedak peel for microwave‐assisted activation. Issue 1 (19th December 2016) - Alias, N.; Zaini, M.A.A.; Kamaruddin, M.J.; You, K.Y.
Abstract: This study was aimed to evaluate the dielectric properties of cempedak peel ( Artocarpus chempeden, A. integer ) impregnated with potassium carbonate. The materials were characterized by moisture content, elemental composition and thermal profile. The dielectric properties were examined using open‐ended coaxial probe method at microwave frequencies and different temperatures. Results show that the dielectric properties changed with frequency, temperature, potassium carbonate impregnation ratio, moisture content and carbon content. Cempedak peel exhibits a better microwave absorber at 25 °C because of higher tan δ than char and impregnated samples. Char displayed a higher tan δ at 35 °C probably because of high carbon content (63.7%). Moisture content and carbon content have to be taken into account in microwave‐assisted activation of cempedak peel. Potassium carbonate can act as microwave absorber to enhance the efficiency of microwave heating for low loss material. Copyright © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.